Disruption of 5-HT1A function in adolescence but not early adulthood leads to sustained increases of anxiety. (3rd May 2016) - Garcia-Garcia, A.L.; Meng, Q.; Richardson-Jones, J.; Dranovsky, A.; Leonardo, E.D.
Highlights: Temporary loss of 5-HT1A function after P35, but not after P50, results in increased anxiety-like behaviors in adulthood. Adolescent blockade of 5-HT1A receptors results in long-term changes in serotonin levels. Adult anxiety phenotype correlates with increased serotonin levels in select brain regions. Brief interventions in the 5-HT system during adolescence lead to profound and enduring changes in behavior. Abstract: Current evidence suggests that anxiety disorders have developmental origins. Early insults to the circuits that sub-serve emotional regulation are thought to cause disease later in life. Evidence from studies in mice demonstrate that the serotonergic system in general, and serotonin 1A (5-HT1A ) receptors in particular, are critical during the early postnatal period for the normal development of circuits that subserve anxious behavior. However, little is known about the role of serotonin signaling through 5-HT1A receptors between the emergence of normal anxiety behavior after weaning, and the mature adult phenotype. Here, we use both transgenic and pharmacological approaches in male mice, to identify a sensitive period for 5-HT1A function in the stabilization of circuits mediating anxious behavior during adolescence. Using a transgenic approach we show that suppression of 5-HT1A receptor expression beginning in early adolescence results in an anxiety-like phenotype in the open field test. We further demonstrate that treatment with the 5-HT1A antagonist WAY 100, 635 between postnatal day (P)35 and P50, but not at later timepoints, results in altered anxiety in ethologically based conflict tests like the open field test and elevated plus maze. This change in anxiety behavior occurs without impacting behavior in the more depression-related sucrose preference test or forced swim test. The treatment with WAY 100, 635 does not affect adult 5-HT1A expression levels, but leads to increased expression of the serotonin transporter in the raphe, along with enhanced serotonin levels in both the prefrontal cortex and raphe that correlate with the behavioral changes observed in adult mice. This work demonstrates that signaling through 5-HT1A receptors during adolescence (a time when pathological anxiety emerges), but not early adulthood, is critical in regulating anxiety setpoints. These data suggest the possibility that brief interventions in the serotonergic system during adolescence could lead to profound and enduring changes in physiology and behavior.